Public policy and citizen-based practices that support social and health services for official and co-official language minority communities. An international perspective: What has really been achieved and what are the gaps | Politiques publiques et pratiques citoyennes soutenant les services sociaux et de santé pour les communautés minoritaires de langue officielle et coofficielles. Une perspective internationale : ce qui a été accompli et ce qui reste à faire - Bouchard, Louise; Nyqvist, Fredrica; Mari Mayans, Isidor; van Kemenade, Solange; Maisonneuve, Alexander. R. (Linguistic Minorities and Society / Minorités linguistiques et société, 2021)

Barrières linguistiques dans l'accès aux soins de santé - Bowen, Sarah (Santé Canada, 2001)

Impact des barrières linguistiques sur la sécurité des patients et la qualité des soins. Rapport final - Bowen, Sarah (Société Santé en français, 2015)

Language barriers in access to health care - Bowen, Sarah (Health Canada, 2001)

Language barriers within the Winnipeg regional health authority. Evidence and implications - Bowen, Sarah (Winnipeg Regional Health Authority, 2004)

The impact of language barriers on patient safety and quality of care. Final report - Bowen, Sarah (Société Santé en français, 2015)

Comparaisons internationales : un aperçu de l'accès aux soins de santé pour les communautés de langue officielle en situation minoritaire au Canada, en Espagne, en Belgique et en Finlande - Bureau d'appui aux communautés de langue officielle (Santé Canada, 2007)

Language barriers and healthcare access: a qualitative study in the Volta Region of Ghana - Glover-Meni, Nathaniel; Nyarko, Joy Ato; Agbezorlie, Peter K.; Agyei, Dominic Dankwah (Journal of Communication in Healthcare, 2024)
Background The study explores the language barriers between two language minority populations and healthcare professionals in the Volta Region of Ghana. Methods An interpretive description with a qualitative approach to data collection and analysis was used. This study was carried out in the Tafi-Atome and Avatime-Vane communities, the Hohoe Municipal Hospital and the Margaret Marquart Catholic Hospital in the Kpando Municipality. In all, 46 respondents comprising 19 purposively sampled community members (patients) from the two selected communities and 27 conveniently sampled healthcare professionals from the two health facilities were interviewed. The face-to-face in-depth interviews were audio-recorded, transcribed and thematically analysed. Results The study revealed a barrier in language use between healthcare professionals and patients from the two language minority communities. While healthcare professionals preferred to use English, Akan and Ewe, the patients, on the other hand, preferred their native languages, which are Sideme and Tegbor. The services of unqualified interpreters were utilised by both healthcare professionals and patients. Study participants were aware of these challenges, which prevented the patients from receiving optimum healthcare services, and the healthcare workers from delivering client-centred healthcare services. Conclusions The presence of communication challenges emanating from language barriers between healthcare professionals and patients should be considered as a key hindrance to the attainment of the Sustainable Development Goal Three (SDG3), which aims to promote health and well-being at all ages. Therefore, stakeholders in the healthcare delivery system in Ghana need to prioritize stronger communication and translation practices and policies.

Communicative sensitivity in the bilingual healthcare setting: A qualitative study of language awareness - Irvine, Fiona. E.; Roberts, Gwerfyl. W.; Jones, Peter; Spencer, Llinos. H.; Baker, Colin. R.; Williams, Cen (Journal of Advanced Nursing, 2006)
Aim. This paper reports on the second phase of a national study in Wales. The research aimed to assess the level of Welsh language awareness amongst healthcare professionals across Wales, and to identify the factors that enhance language choice within service delivery. Background. The literature suggests that language sensitive healthcare practice is central to ensuring high quality care. However, it is evident that language barriers continue to compromise the quality of care within nursing and other health services. One issue that has received little attention is the level of language awareness that healthcare professionals currently demonstrate. Furthermore the factors that influence language choice for bilingual/multilingual speakers are not well explored in the literature. Methods. The study involved semi-structured interviews with a range of healthcare professionals in acute and community settings across Wales. Using a systematic sampling matrix, a purposeful sample of 83 professionals was selected to participate. Twenty-seven of the respondents were nurses, health visitors and midwives. The interviews focussed on the factors that facilitate or impede language sensitive healthcare practice. All interviews were audiotaped and, using a framework analysis approach, conceptual codes were developed and defined and categories and sub-categories were constructed to create thematic charts. Findings. Three main themes were identified: care enhancement, which focussed on the process and outcome of offering language choice to bilingual patients; organizational issues, which reflected issues relating to the infrastructure of service provision; and training implications, which focused on Welsh language learning in health care. Conclusions. Complex dynamics of language use are in operation within bilingual healthcare settings and organizational as well as individual factors are important in facilitating appropriate language use. Many of the issues highlighted are not peculiar to the Welsh context, but apply to healthcare settings across the world, where other minority languages are in use.

Approach to the status and management of languages in the catalan public health care system - Pere Mas, Jordi (Linguistic Minorities and Society, 2021)
This article deals with the situation of languages in healthcare in Catalonia. It reports on the measures being carried out by the Ministry of Health of the Government of Catalonia to guarantee that the population may be attended to in their own official language, whether Catalan, Spanish or Occitan, and specifically to promote knowledge and use of Catalan among professionals working in the health system. It provides data on the migratory flows of doctors and nurses and sociolinguistic data. Other sections deal with healthcare services provided in non-official languages and in Catalan sign language, as well as language-related complaints and the measures implemented to make Catalan a suitable and prestigious language for medical and scientific communication. It concludes by listing the challenges that still need to be tackled to give Catalan greater presence and to raise its status in the field of health. Keywords: healthcare, health, Catalan, linguistic planning, healthcare professionals, official languages, Catalonia

Comparing mental health of Francophones in Canada, France, and Belgium: 12-month and lifetime rates of mental health service use (part 2) - Tempier, Raymond; Vasiliadis, Helen-Maria; Gilbert, Fabien; Demyttenaere, Koen; Bruffaerts, Ronny; Lépine, Jean-Pierre; Gasquet, Isabelle; Lepnurm, Marje; Lesage, Alain; Puchala, Chassidy; Mosier, Karen; Kovess-Masféty, Viviane (The Canadian Journal of Psychiatry, 2010)
Objectives: To compare 12-month and lifetime service use for common mental disorders in 4 francophone subsamples using data from national mental health surveys in Canada, Quebec, France, and Belgium. This is the second article in a 2-part series comparing mental disorders and service use prevalence of French-speaking populations. Methods: Comparable World Mental Health-Composite International Diagnostic Interviews (WMH-CIDI) were administered to representative samples of adults (aged 18 years and older) in Canada during 2002 and in France and Belgium from 2001 to 2003. Two groups of francophone adults in Canada, in Quebec (n = 7571) and outside Quebec (n = 500), and respondents in Belgium (n = 389) and France (n = 1436) completed the French version of the population survey. Prevalence rates of common mental health service use were examined for major depressive episodes and specific anxiety disorders (that is, agoraphobia, social phobia, and panic disorder). Results: Overall, most francophones with mental disorders do not seek treatment. Canadians consulted more mental health professionals than their European counterparts, with the exception of psychiatrists. Conclusions: Patterns of service use are similar among francophone populations. Variations that exist may be accounted for by differences in health care resources, health care systems, and health insurance coverage.

La santé et les minorités linguistiques : l’approche canadienne au regard de cas internationaux - Traisnel, Christophe; Forgues, Éric (Francophonies d'Amérique, 2009)
Dans notre article, nous présentons une analyse comparative de l’approche canadienne de l’enjeu de la santé pour les communautés francophones en situation minoritaire (CFSM). Nous montrons que l’État canadien a favorisé une démarche de concertation avec les acteurs communautaires. Notre analyse comparative nous a permis de dégager une typologie des politiques linguistiques en matière de santé destinées aux CFSM. Cette typologie permet de situer l’expérience canadienne par rapport à d’autres expériences, parfois proches, mais présentant des perspectives différentes, comme le montrent les cas finlandais, belge et états-unien. La « voie » canadienne paraît originale dans la mesure où elle semble se situer entre un modèle communautaire, à l’instar des pays européens, et un modèle individualisé, à l’instar de ce qui se fait aux États-Unis.